Moderating effects of the valence of social interaction on the dysfunctional consequences of perseverative cognition: an ecological study in major depression and social anxiety disorder. Issue 2 (4th March 2019) - Bailey, T.; Shahabi, L.; Tarvainen, M.; Shapiro, D.; Ottaviani, C.
ABSTRACT : Background and Objectives: Major depression disorder (MDD) and social anxiety disorder (SAD) are characterized by the use of perseverative cognition (PC) as a dysfunctional coping strategy. We sought to investigate the dysfunctional physiological and psychological consequences of PC and how the valence of social interactions moderates such consequences in these psychopathological conditions. Design/Methods: The study combined 24-hour heart rate variability (HRV) and ecological momentary assessments in 48 individuals with MDD, SAD, and sex-matched controls. Results: In all participants, PC was associated with mood worsening and reduced ability of the parasympathetic nervous system, mainly the vagus, to inhibit sympathetic arousal (i.e., reduced HRV). Individuals with SAD had the highest frequency of daily PC, while those with MDD reported that PC interfered more with their ongoing activities. In SAD, daily PC was associated with significantly lower HRV after negative social interactions. Individuals with MDD reported higher levels of sadness during PC irrespective of the valence of the preceding social interaction but higher levels of anxiety and efforts to inhibit PC following positive interactions. Conclusions: Results highlight the need to account for important moderators like the valence of social interaction when looking at the physiological consequences of maladaptive emotion regulation strategies.